Impacts of glyphosate-based herbicides on soil microbiota - Liyanage, Pawani (My University, 2025)
The present study investigates long term effects of glyphosate-based herbicides (GBHs) on soil microbes. GBHs inhibit the 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) enzyme in the shikimate pathway of plants, eventually eliminating weeds from agricultural fields. However, several microbes have shikimate pathway and there is very little information on the long-term effects of GBHs on soil bacteria. The study used bacterial culturing techniques, glyphosate-sensitivity prediction bioinformatics tool and in vitro glyphosate sensitivity tests to investigate the response of soil bacteria collected from an experimental plot with long-term GBH application. Bacterial colony formation was decreased in soil samples collected from GBH-treated plots compared to the control plot. The abundance of cultured bacteria was lower in the samples from GBH-treated soil compared to that of control soil. Even though, GBH treatment did not significantly change the overall bacterial diversity in terms of number of taxa, bacterial richness and evenness in genus level were notably impacted by GBH exposure. Phyla Pseudomonadota was more dominant while Actinomycetota, Bacillota, and Bacteroidota were less dominant in samples from GBH-treated plots compared to those from control plots. Glyphosate sensitivity assays showed variable observations in low and high GBH treatments, when compared to the predictions of EPSPS bioinformatics tool. Most isolates grew in low GBH regardless of predicted sensitivity status or source of sample origin (control or GBH plots). However, except for genus Variovorax, Sphingomonas and Pseudarthrobacter none of the selected isolates grew in high GBH. Remarkably, Variovorax and Pseudarthrobacter bacterial isolates from GBH-treated plots were resistant to even high GBH treatment whereas those from control plots did not grow. The findings reveal that GBH effect on bacterial growth depends on the applied quantity of the glyphosate, with higher concentrations potentially inhibiting growth while lower concentrations might have stimulated the development of resistant mechanisms. Further studies are essential to deeply understand the response of each bacterial taxa to long-term field application of GBH and how it may affect microbial interactions and soil health.
Keywords: GBH, Bacterial diversity, bacterial community composition, shikimate pathway, long term effects, Glyphosate sensitivity